Adiwiyata (Green School) Program Optimization Strategy in Malang Regency to Realize Environmentally Friendly School Citizens - Hana Naqiyya Nada; Rhina Uchyani Fajarningsih; Okid Parama Astirin (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2021)
Globalization encourages rampant development by exploiting natural resources on a large scale. Adiwiyata program is a manifestation of environmental education to raise awareness and concern about the environment. However, the number of Adiwiyata schools is still small, and its implementation has met challenges and obstacles. The research aims to formulate a development strategy for the Adiwiyata program to run optimally and achieve the goals. The research was conducted in Adiwiyata elementary school, junior high, and high school level in Malang regency consisting of Adiwiyata Award school (National or Independent) and Adiwiyata non-Award (District or Province).The study used a qualitative descriptive method with IFAS and EFAS matrices, and then a SWOT and QSPM analysis was performed. The results revealed that Adiwiyata program implementation in Malang Regency was carried out quite well. Several supporting factors and obstacles came from inside and outside the school. The planning and growth strategies were formulated for the Adiwiyata non-awarded schools in quadrant II (2.24; -0.08), while the rewarded Adiwiyata schools were in quadrant I (2.35; 2.88) with alternative development and sustainability strategies. The strategy formulation results are expected to be used as a reference in the development of the Adiwiyata program in Malang Regency.